ANALISIS KONSEP MONOPOLI DALAM TRANSAKSI EKONOMI SYARIAH - Rizky Wahyu Pranata; Fauzatul Laily Nisa (JURNAL ILMIAH EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2024)
Monopoly in the context of sharia economics is referred to as "ihtikar" or hoarding behavior, which is prohibited because it can disrupt market mechanisms and economic balance. Nevertheless, there are cases where monopoly can be allowed if the goal is to achieve people's prosperity. This research uses a qualitative descriptive approach with a literature study method to gain a comprehensive understanding of various financing models in sharia economics. The research results indicate the need for further research to understand the impact and implications of monopoly in sharia economic transactions. An in-depth analysis of the concept of monopoly in the context of sharia economics can help identify solutions or strategies that are in accordance with sharia economic principles to prevent and overcome monopoly practices that are detrimental to society. The need for an effective regulatory role in supervising the market so that it remains healthy and competitive, along with the importance of broader awareness and understanding of the relationship between sharia economic principles and conventional economic concepts such as monopoly.